PHYSICAL EXERCISE IN FRAGILE ELDERLY PEOPLE WITH SARCOPENIA: A BRIEF LITERATURE REVIEW - Galvão de Souza, Alice; Antunes Leite, Camila; Valvano Filho, Marcelo; Teixeira João, Priscila; Carlos Brech, Guilherme; Doro, Marcio (Health and Society, 2023)
Sarcopenia and physical frailty have been affecting a large part of the elderly population around the world, this brief review aimed to relate physical exercise with the prevention and treatment of sarcopenia in frail elderly. 179 articles were found that were selected according to the inclusion criteria, field research with at least 20 subjects, study with intervention (acute study should not be selected), after applying the exclusion criteria, four studies were selected that elucidated the discussion of this article. Studies that use physical exercise both in the treatment and prevention of sarcopenia bring significant results that indicate a great improvement in the clinical condition of the elderly.